Peran Sambang oleh Bhabinkamtibmas dalam Mencegah Pencurian Kendaraan Roda Dua di Polsek Cirebon Utara Barat: Peran Sambang oleh Bhabinkamtibmas dalam Mencegah Pencurian Kendaraan Roda Dua di Polsek Cirebon Utara Barat - ALI, MUHAMMAD RIZKY (Advances in Police Science Research Journal, 2017)
This research is motivated by the highest number of two-wheeled motor vehicle theft in the Cirebon City Police area. The existence of these problems, Bhabinkamtibmas North Cirebon West Sector Police has a role to prevent the crime of theft of two-wheeled motorized vehicles so that it does not occur in the area of ​​North Cirebon West Sector Police through the sambang. Therefore, by conducting research to find out the implementation of the symbol by Bhabinkamtibmas using a qualitative approach, using field research methods, as well as data collection techniques by interviewing, observing, and studying documents to be able to find out the competencies owned by Bhabinkamtibmas and the factors that influence the implementation the sambang. The results of the research and discussion of this study indicate that the implementation of the sambang by Bhabinkamtibmas by implementing planning, organizing, implementing and controlling there are still shortages namely not introducing themselves during the implementation of the sambang and there is a lack of equipment that does not support the implementation of the sambang. The technical competency aspect of Bhabinkamtibmas has not fulfilled general competence because only one Bhabinkamtibmas has carried out vocational education. So that the level of education is still not sufficient. And by analyzing the factors that influence the implementation of the symbol by Bhabinkamtibmas there are factors in the form of internal factors and external factors. Overcoming this problem, the authors suggest that Bhabinkamtibmas continue to implement according to the regulations and propose procurement of equipment such as modems, computers and printers. Giving rewards from the leadership for the performance of Bhabinkamtibmas with achievements, for example by including vocational education, Bhabinkamtibmas should be from the fostered villagers, advice to the Leadership for a sambang targeting official homes accompanied by Binmas in plain view and submitting his own official residence for Bhabinkamtibmas. Keywords: role of sambang, Bhabinkamibmas, theft of two-wheeled motor vehicles. and North Cirebon West Sector Police.